Impact of season, age and breed on semen microbial load andits association with semen quality in prominent Indian goat breeds - VERMA, ABHISHEK KUMAR; SINGH, BHOOPENDRA; SRIVASTAVA, SUSHANT; ALAM, KABIR; VERMA, SANJEEV KUMAR; VERMA, RAJESH KUMAR; SAURABH; KUMAR, RABINDRA; KUMAR, RAJESH; JAISWAL, ANKIT (The Indian Journal of Animal Sciences, 2026)
The aim of this study was to estimate the occurrence of bacteriospermia, determine the bacterial load in fresh semen from 2–6-year-old bucks, and assess the association between bacterial load and sperm quality traits in various Indian goat breeds. For the experiment, one hundred forty-four (144) fresh semen ejaculates were obtained from six bucks of various breeds (two bucks from each breed: Jamnapari, Sirohi, and Barbari) using a sterile artificial vagina on a weekly basis, adhering to a standardized collection technique during three distinct seasons (summer, rainy, and winter). After initial evaluation, samples were subjected to bacteriological examination. The total viable bacterial count of fresh semen was measured using the standard plate count method. The results indicated that the bacterial load was 70%, 56.66%, and 63.33% in Sirohi, Jamnapari, and Barbari bucks, respectively. Sirohi bucks exhibited higher bacterial counts (458.36 ± 9.35 CFU/mL) compared to both Barbari (419.28 ± 10.23 CFU/mL) and Jamnapari (413.82 ± 9.77 CFU/mL). An age-wise analysis revealed that older bucks (≥5 years: 456.73±12.56 CFU/mL) had significantly greater microbial loads than younger groups (2.5–3.5 years: 406.90±4.33 CFU/mL; 3.5–5 years: 423.40±9.53 CFU/mL). Microbial loads in rainy season were significant (p